PERAN PROTEIN SIKLIN DALAM REGULASI SIKLUS SEL DAN IMPLIKASINYA TERHADAP PENYAKIT: SUATU TINJAUAN LITERATUR - Suharni, Suharni (Yayasan Nusantara Hasana Berdikari, 2026)
The cell cycle is a biological process that regulates growth, genetic replication, and cell division in a coordinated manner to maintain tissue homeostasis. Regulation of this process depends on the integrated interactions between cyclin proteins (cyclins), cyclin-dependent kinases (CDKs), cyclin-dependent kinase inhibitors (CKIs), and various checkpoint proteins. Cyclin proteins function as master regulators, specifically activating CDKs at each phase of the cell cycle, ensuring the orderly transitions between G1, S, G2, and M phases. The activity of the cyclin-CDK complex is controlled through mechanisms of synthesis, degradation by the ubiquitin-proteasome system, and checkpoint surveillance, ensuring accurate DNA replication and cell division. Disruption of this system leads to uncontrolled cell proliferation, genomic instability, checkpoint failure, and an increased risk of various diseases, particularly cancer. In addition to its role in oncogenesis, dysregulation of cyclin proteins is also associated with cellular aging, impaired tissue regeneration, and several neurodegenerative diseases. Advances in molecular biology have made the cyclin-CDK pathway a key target for precision therapy, as evidenced by the successful development of CDK4/6 inhibitors in various cancers. This review article discusses the regulatory mechanisms of cyclin proteins in the cell cycle, their roles at each phase of cell division, the clinical implications of dysregulation, and the development of targeted therapies based on current scientific evidence.